Calcium deficiency in hydroxyapatite and its drug delivery applications. (1st April 2018) - Koppala, Sivasankar; Swamiappan, Sasikumar; Gangarajula, Yuvaraj; Xu, Lei; Sadasivuni, Kishor Kumar; Ponnamma, Deepalekshmi; Rajagopalan, Vijayaraghavan
Abstract : In this work, calcium deficient hydroxyapatites (HAPs) [Ca10− x (PO4 )6 (OH)2 ] [where x = 0 − 0.3] were synthesised by precipitation method and calcined samples were characterised by Fourier transformation infrared spectroscopy, powder X‐ray diffraction, scanning electron microscopy and energy‐dispersive X‐ray spectroscopy techniques to check phase purity, calcium deficiency, particle size and shape. The results indicate that the structure of the HAP can tolerate a calcium deficiency up to 0.2. The calcium deficient HAP ( x = 0.1) powder was found to be highly porous with a particle size below 200 nm. This powder was used as a drug delivery carrier for the drug, ciprofloxacin and sustained release of the drug in the phosphate buffer solution was investigated.